A two-step approach for size controlled preparation of monodisperse polysaccharide-based nanospheres. (6th February 2019) - Chu, Lin; Niu, Wenbin; Wu, Suli; Ma, Wei; Tang, Bingtao; Zhang, Shufen; Li, Heping; Liu, Zheng
Abstract: Owing to the simultaneous occurrence of nucleation and nuclei aggregation in nanoprecipitation approach, the preparation of monodisperse nanospheres from polysaccharide remains a great challenge. Herein a two-step approach is presented for size controlled preparation of monodisperse polysaccharide-based nanospheres with PDI of 0.05 from starch acetate (SA). First, the starch acetate nanospheres (SANs) with average size in the range from 100 to 160 nm were produced by a moderate and constant hydrophobic interaction (MCHI) process. Second, based on principle of Ostwald ripening, a facile hydrothermal method was employed to modulate the size of the SANs obtained from the first step, yielding monodisperse nanospheres ranging from 200 to 1400 nm. This two-step method was also successfully applied to the preparation of ethyl cellulose nanospheres, which provided a facile strategy to prepare nanospheres from polysaccharides. Finally, SANs (744 nm) and ECNs (802 nm) were used to fabricate 2D photonic crystals by self-assembly, further verifying high monodispersity of obtained polysaccharide-based nanospheres.